2013
DOI: 10.1155/2013/212767
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Processing Speed in Executive Function Immediately following an Increase in Cardiovascular Activity

Abstract: This study aims to identify the acute effects of physical exercise on specific cognitive functions immediately following an increase in cardiovascular activity. Stair-climbing exercise is used to increase the cardiovascular output of human subjects. The color-naming Stroop Test was used to identify the cognitive improvements in executive function with respect to processing speed and error rate. The study compared the Stroop results before and immediately after exercise and before and after nonexercise, as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…The discrepancy between GNG results and Stroop results in the current study suggests that, even among response inhibition tasks, there are differences in effect of exercise, a finding which is consistent with prior research (68). Specifically, while a number of studies have shown improvement in Stroop performance (40,41,46,(69)(70)(71), results for GNG have been inconsistent (72,73). This finding suggests that Stroop, but not GNG performance, is significantly improved following acute aerobic exercise; however, future research is needed to confirm these findings.…”
Section: Discussionsupporting
confidence: 81%
“…The discrepancy between GNG results and Stroop results in the current study suggests that, even among response inhibition tasks, there are differences in effect of exercise, a finding which is consistent with prior research (68). Specifically, while a number of studies have shown improvement in Stroop performance (40,41,46,(69)(70)(71), results for GNG have been inconsistent (72,73). This finding suggests that Stroop, but not GNG performance, is significantly improved following acute aerobic exercise; however, future research is needed to confirm these findings.…”
Section: Discussionsupporting
confidence: 81%
“…(Alves et al, 2012) and the other with high school students (Harveson et al, 2016), both of which demonstrated an improvement in EF following both aerobic and resistance exercise. The fact that acute aerobic exercise improves EF is well documented (e.g., Byun et al, 2014;Tam, 2013).…”
Section: Figurementioning
confidence: 99%
“…Acute moderate-intensity aerobic exercise was found to improve EF, as indicated by higher scores in the interference phase of the Stroop test in endurance athletes (Hogervorst, Riedel, Jeukendrup, & Jolles, http://www.ac-psych.org 2019 • volume 15(3) • 208-215 209 1996), and in young adults (Tam, 2013). Interestingly, the improvement in the interference phase of executive control in young athletes was explained by improved attention (Chang, Pesce, Chiang, Kuo, & Fong, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on studies included in this analysis, there seems to be some benefit of aerobic exercise on PD symptoms, with indications that exercise might improve EF, including judgment and attention in the presence and absence of depression (40,41,49).…”
Section: Aerobic Exercise Physical Therapy Physiotherapy and Executmentioning
confidence: 99%